Peran orang tua dalam pendidikan karakter peserta didik selama pembelajaran online - Amelia Haryanti; Dindin Dindin (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2021)
The purpose of this research is to find out the role of parents / guardians of learners in helping the character of learners during online learning in the covid-19 pandemic and the obstacles faced by parents during online learning. This research method uses a qualitative approach with case studies. The research subjects used were parents / guardians of learners in Pondok Benda Village, Pamulang District of South Tangerang City. Data collection techniques use observation, documentation, and interviews. The results of the research obtained are as follows: Parents are more trying to foster the character values of learners during online learning, parents provide real examples between subject matter and real examples in everyday life that can be witnessed and felt directly by learners in the environment where they live, while the obstacles faced by parents are the way of delivery in providing understanding of learning materials to learners, Not as good as teachers in school. To overcome these problems parents create a group with Civic Education teachers to jointly conduct supervision and consultation related to learning materials so that learners are maximal in understanding learning during online learning.